Death is not a success: Reflections on business exit. (November 2014) - Coad, Alex
This article is a critical evaluation of claims that business exits should not be seen as failures, on the grounds that may constitute voluntary liquidation, or because they are learning opportunities. This can be seen as further evidence of bias affecting entrepreneurship research, where failures are repackaged as successes. This article reiterates that the majority of business exits are unsuccessful. Drawing on ideas from the organisational life course, it is suggested that business 'death' is a suitable term for describing business closure. Even cases of voluntary 'harvest liquidation' such as retirement can be meaningfully described as business deaths.